The effects of Web 2.0 supported environmental education on self-efficacy belief regarding environmental education and environmental awareness - Küçükaydın, Menşure Alkış; Ulum, Hakan (Education and information technologies, 2023)
The aim of this study is to determine the effects of Web 2.0 supported environmental education on self-efficacy belief regarding environmental education and environmental awareness of teacher candidates studying in the primary school teacher program. The study took on a quasi-experimental design with a pre-test and post-test control group. There were 33 teacher candidates in the experimental group and 32 teacher candidates in the control group. The study was carried out with teacher candidates studying in their first year and enrolled in the Environmental Education course. While environmental education was carried out in the Web 2.0 environment with the students in the experimental group, environmental subjects were covered in the school environment in the control group. Data were collected with the Scale of Self-Efficacy Belief Regarding Environmental Education (SEEE) and the Environmental Awareness Scale. In data analysis, independent sample t-tests and two-way ANOVA were used for repeated measurements. The results of the analysis showed that Web 2.0 supported environmental education led to a statistically significant difference in the academic competence perception of SEEE, although Web 2.0 supported teaching did not have an effect on environmental awareness. The findings present different perspectives on the use of Web 2.0 technologies in environmental education.